STUDI PEMANFAATAN INTERNET DALAM PROSES PENULISAN SKRIPSI MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP - 910-928 , Akbar Vilhayati (Universitas Negeri Padang, 2016)
AbstractThe purpose of this research is to reveal the use of the internet in the writing of student majoring in civil engineering faculty of the state university engineering of padang. This research started from known yet exactly how the study of internet use in the procces of writing a thesis student majoring in civil engineering, related to the use of browser and browsing, searching to find articles using paper materials, read and download material from the internet, use the chat facility, action on search results and quoting from the internet.This is a descriptive research. Population in this research were 51 students majoring in civil engineering faculty of the state university engineering of padang that are in the procces of thesis writing, 33 people among the research sample taken form a strtified random sampling technique , in tis study the instrument used was a questionnaire using likert scale. Data analysis using descriptive analysis and calculation of the percentage.The result of this research indicate that the use of the internet in procces of writing a thesis by students majoring in civil engineering of padang in the category enough. The results found on the utilization of faculty utilization browser and browsing is 81,06% included in good category, the results of the use of searching to find articles and thesis is 80, 55% included in good category, the results of reading and downloading material from the internet is 77,27% included in enough category, the results of the use of the chat facility is 82,275 inluded to good category, the results of the action on the search result is 77,02% include in the enough category and the result of the way the internet is quoting from 66,91% included in enough category Key Word: Writing of thesis, Internet